Effects of selected factors on the osseointegration of dental implants - Koszuta, Piotr; Grafka, Agnieszka; Koszuta, Agnieszka; Łopucki, Maciej; Szymańska, Jolanta (Menopause Review/Przegląd Menopauzalny, 2015)
Introduction : Osseointegration of dental implants with the maxillary and/or mandibular bone is the basis for implant prosthetic treatment. The aim of the study was to assess the influence of the patients’ gender, age, and in the case of women, their menopausal status (before menopause/after menopause/during hormone replacement therapy) on the osseointegration of dental implants. Material and methods : The study evaluated the bone loss after implant loading and the success rate of the procedure in 71 women and 30 men. In the postmenopausal group, 20 (28.1%) women were receiving hormone replacement therapy. The implants used in the treatment of the studied patients were the two-phase dental implants. The extent of bone loss was estimated by comparing the post-implantation radiographs and the post-loading ones. Results : The implantation procedure was entirely successful in 81 patients (80.2%). The patients’ age, gender and menopausal status did not significantly affect the implantation procedure success rate or bone loss (p > 0.05). A correlation between bone loss and hormone replacement therapy (p = 0.002) was found. Conclusions : The hormone replacement therapy contributes to a greater peri-implant bone loss. The patients receiving hormone replacement therapy who consider replacement of missing teeth with implants should be informed about a greater risk of osseointegration failure, which may affect the success of implant therapy.